Peran Generasi Z Muslim dalam Kemajuan Islam di Era Modern: Pandangan Ustadz Hanan Attaki - Alfina Meiza Faysa; Mila Hanifah; Muhamad Ariz Hibrizi; Virza Qurrota A’yun; Abdul Fadhil (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article examines the role of the Muslim Gen Z in the advancement of Islam in the modern era based on the views of Ustadz Hanan Attaki. Generation Z, known as the tech-savvy and creative generation, has great potential in facing the challenges and opportunities of da'wah in the digital era. Based on the lectures and views of Ustadz Hanan Attaki, this article highlights three main roles of Muslim Gen Z: first, as ambassadors of Islam who can utilize social media to spread moderate and relevant Islamic values; second, as innovators contributing to the development of science, technology, and art in accordance with Islamic values; and third, as guardians of Islamic identity amidst the currents of globalization and secularism. This research uses qualitative methods with data collection techniques such as observation and literature review. This research concludes that Muslim Generation Z, with proper guidance, can become agents of change who significantly contribute to the advancement of Islam in the modern era.